High-risk Human Papillomavirus Determination in Formalin-fixed, Paraffin-embedded Cervical Tissue Using the Roche Cobas 4800 System: A Comparative Study With Liquid-based Cytology. (January 2019) - Tardío, Juan C.; Cambero, Olivia; Sánchez-Estévez, Carolina; Sánchez-García, Ana B.; Angulo, Fernando; Moreno, Amalia
Abstract : Roche cobas 4800 human papillomavirus (HPV) test is an automated real-time polymerase chain reaction–based system that allows the simultaneous detection of 14 human papillomavirus high-risk (HR-HPV) genotypes. This test is Food and Drug Administration approved since 2011 for HPV determination in liquid-based cytologic samples, but a clinically validated technique for formalin-fixed, paraffin-embedded (FFPE) tissue specimens is presently not commercially available. In our laboratory, we have developed an HPV detection procedure in FFPE tissue by cobas 4800 HPV test. In order to validate our method, we retrospectively studied 165 FFPE cervical biopsy and conization specimens with varied diagnoses from our files. In 50 of them, we contrasted the results with those obtained from simultaneous liquid-based cytologies from the same patients. Finally, seeking the possible complementary clinical usefulness of the procedure, we compared the HPV genotypes detected in cervical intraepithelial neoplasia grade 1 (CIN1)-diagnosed biopsies from 20 patients with a subsequent high-grade CIN (CIN2+) diagnosis with those from another group of 20 patients without a subsequent CIN2+ diagnosis. Eighty-seven percent of the assays provided informative results. HR-HPV was detected in 28 of 32 (88%) invasive cervical squamous carcinomas. Coincidental HR-HPV genotypes were obtained in 32 of 50 (64%) cases with simultaneous cervical biopsy and liquid-based cytologic samples. A significant higher risk of progression to CIN2+ was found when HPV16 ( P =0.022) or any HR-HPV genotype ( P =0.037) was detected in CIN1 biopsies. The reported procedure provides an automated, technically time-saving, easy to integrate into laboratory routine, and reliable method of HR-HPV determination in FFPE specimens.